2011
DOI: 10.21608/ejabf.2011.2088
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical characteristics and heavy metal contents in water of Wadi El-Rayan Lakes, western desert, Egypt.

Abstract: hysico-chemical characteristics and eight heavy metals (Fe, Mn, Cu, Co, Cr, Ni, Pb and Cd) of Wadi El Rayan Lakes water were evaluated from summer 2009 to spring 2010. Salinity (TDS) and major ions show highly significant difference between the two lakes. On the other side, station 1 in 1 st lake (infront El Wadi Drain) exhibits the highest content of nutrient salts and heavy metals.The mean values of Fe, Mn, Cu, Co, Cr, Ni, Pb and Cd in the 1 st lake were 562. 33, 82.71, 15.49, 9.69, 11.86, 11.68, 9.66 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
5
4
0
Order By: Relevance
“…On the other hand, the lowest temperature value (17.5°C ±1.40) was observed at site (A) during winter. Low water temperature during winter is due to high current velocity, frequent clouds and high humidity (Shama et al, 2011). This in agreement with Khalil et al (2012) who found that water temperature was 17.78ºC at Ismailia canal water during winter season.…”
Section: Resultssupporting
confidence: 86%
“…On the other hand, the lowest temperature value (17.5°C ±1.40) was observed at site (A) during winter. Low water temperature during winter is due to high current velocity, frequent clouds and high humidity (Shama et al, 2011). This in agreement with Khalil et al (2012) who found that water temperature was 17.78ºC at Ismailia canal water during winter season.…”
Section: Resultssupporting
confidence: 86%
“…It is the most abundant element of the heavy metals in most Lagoons. This is agreed with the findings of Shama et al (2011). The highest value of iron (48.6 μg/l) was recorded at Damru drain, while the lowest value (10.55 μg/l) was obtained at west of Abou Amer area far from drainage areas.…”
Section: Iron (Fe)supporting
confidence: 92%
“…Regarding seasonal variation, summer exhibited the highest water temperature with an average of 31.6 ºC, while winter exhibited the lowest with an average of 17.78 ºC. The low water temperature during winter and autumn is due to frequent clouds, high humidity, high current velocity, while high water temperature during summer and spring is due to clear atmosphere and great solar radiation (Shama et al, 2011). The analysis of variance (ANOVA) revealed significant regional and seasonal variation (F= 10.99 and 467.457, p< 0.05, respectively).…”
Section: Physico-chemical Parameters: Water Temperaturementioning
confidence: 97%
“…Nitrite was detected only during winter with lower values than the corresponding values of nitrate due to the fast conversion of NO 2 -to NO 3 -ions by nitrifying bacteria (Shama et al, 2011). The increase in NO 2 -during cold seasons might be attributed to low consumption by phytoplankton as well as the oxidation of ammonia by nitrifying bacteria and biological nitrification (Rabeh, 2000 and (Table 8).…”
Section: Nutrientsmentioning
confidence: 99%